Effects of cold physical plasma on oral lichen planus: An in vitro study (Effects of CAP on OLP). (21st November 2020) - Seebauer, Christian; Freund, Eric; Hasse, Sybille; Miller, Vandana; Segebarth, Maria; Lucas, Christian; Kindler, Stefan; Dieke, Tobias; Metelmann, Hans‐Robert; Daeschlein, Georg; Jesse, Katja; Weltmann, Klaus‐Dieter; et al.
Abstract: Objectives: In the search for more effective and safe treatment avenues, we investigated cold physical plasma as a new treatment modality for therapy of oral lichen planus (OLP). Material and Methods: Healthy and diseased human mucosal tissue samples with a size of 3 mm in diameter obtained from OLP patients were subjected to plasma treatment ex vivo or were left untreated. Tissue sections were quantified for immune‐infiltration of CD4 +, CD8 +, CD45RA +, and CD45R0 + T cells. Moreover, the tissues' inflammatory profile was assessed by analyzing 12 different cytokines in the surrounding media. Results: A significantly increased infiltrate of CD8 + and CD45‐R0 + T cells was detected in OLP tissue samples when compared to healthy tissue. A higher concentration of interleukin (IL) 1β, IL6, IL8, and granulocyte macrophage‐colony stimulating factor (GM‐CMF) was detected in OLP samples compared to healthy mucosal tissue. For all cytokines and chemokines investigated, 23 out of 24 comparisons showed a decrease in tendency (significant for IL1β, IL2, IL10, and GM‐CSF) in response to plasma treatment. In ex vivo‐treated tissue, a decrease of T‐cell infiltrate in OLP lesions compared with healthy tissue was observed. Conclusion: Our findings suggest cold physical plasma can be a promising therapeutic option for OLP that requires further validation in vivo.